Brand Equity Mediates Firm-Created Content, User-Generated Content, and Digital Word of Mouth - Putu Winna Maharani Winarta; Oka Martini (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study analyzes the mediating role of brand equity in the relationships between firm-created content (FCC), user-generated content (UGC), and digital word of mouth (dWOM) on purchase intention in the context of social media marketing. A quantitative design with an associative causality approach was employed, with data collected online from TikTok users in Indonesia who had interacted with Mosdoom bag content. Purposive sampling was applied with criteria including being at least 18 years old, residing in Indonesia, and having engaged with Mosdoom-related content within the last three months, yielding 140 valid responses based on Hair’s formula. Data were obtained through differential-scale questionnaires and analyzed using regression techniques to examine direct and indirect effects. The findings demonstrate that FCC, UGC, and dWOM each exert positive and significant effects on brand equity and purchase intention, while brand equity itself significantly enhances purchase intention. Furthermore, brand equity is confirmed to play a significant mediating role in strengthening the influence of FCC, UGC, and dWOM on purchase intention. These results highlight the strategic importance of brand equity in digital consumer behavior, offering theoretical contributions to the literature on social media marketing and practical implications for firms seeking to optimize consumer engagement and purchasing decisions.